Evaluation on soil quality under community based agroforestry system - a case study on soil's under homegarden practices at Sabal Kruin village - Ong, Gabriel Ooi Seng (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Homegarden, which mimics natural multilayered forest consisting of diversified agricultural crops and multipurpose trees, although producing small amount of food yields, but the yields are sustained and stable, high variety and yet low input use. Although homegarden practice is also widely practiced in Malaysia on a small-scale or household basis, however, in-depth ecology and socioeconomic study on this practice particularly in Sarawak region is still limite~Therefore, the main objective of this study is to characterize the soil properties ofhome garden practice under different crops, i.e. vegetables and fruits, and also to identify the homegarden management by the households in Kruin village, Sabal. Soil samples were collected at the depths of 0-10cm and 30-40cm for soil physicochemical properties. Among the properties measured were total nitrogen content (N), pH in water, bulk density and soil organic matter (SOM) content. The result showed that the soils for homegardens were sandy in texture, high in pH (6.51±0.86) and bulk density (1.41±O.lO gmL-1), in addition with low SOM (2.79±0.64 %) and total Kjeldahl nitrogen (1.11±0.23 g/kg). The reasons for these characteristics include parent materials and homegarden management. The result also showed that the soil properties of fruit gardens were similar to the secondary forests, with no significant difference between the soil properties of both surface and subsurface soils. The results showed both homegarden and fruit gardens have relatively low maintenance level especially in fertilizer application and it can be concluded that these two land use system does not show much impact to the soil. However, further detail investigation on the soil must also be made to clarify the effects of homegarden practice and to predict the sustainability of the practice in long run.